The Changing MR Imaging Appearance of Polymicrogyria: A Consequence of Myelination - Takanashi, Jun-ichi; Barkovich, A. James (American journal of neuroradiology : AJNR, 2003)
During the review of MR studies of multiple patients with polymicrogyria (PMG), it was noted that the patterns of cortical abnormality differed significantly among affected patients. In particular, the cortex appeared very thin in some patients, but was thick in others. The purpose of the present study was to attempt to clarify the cause of the different imaging appearances. T1- and T2-weighted images obtained in 17 patients (age range, 3 days to 43 years) with PMG diagnosed on the basis of imaging characteristics were retrospectively reviewed. One patient was examined four times over a period of 21 months. Particular attention was paid to the thickness and signal intensity of the cortex and underlying white matter and how these features varied with maturation of the cortex and white matter. T2-weighted images revealed two patterns of PMG. Pattern 1 showed small, fine, and undulating cortex with normal thickness (3-4 mm) in seven patients, all younger than 12 months; and pattern 2, a bumpy cortex that appeared abnormally thick (6-8 mm) and had an irregular cortical-white matter junction in seven patients older than 18 months. Both patterns were observed in four patients between 15 months and 2 years of age (ie, pattern 1 in the anterior frontal region and pattern 2 in the posterior frontal, parietal, or perisylvian regions). A layer of T2 prolongation (2-3 mm) was recognized between pattern 1 PMG and underlying myelinated white matter in four patients 11 months to 2 years of age. T1-weighted images showed either poor differentiation of the cortex and underlying white matter or pattern 2. Serial MR imaging in one patient depicted longitudinal changes of the PMG from pattern 1 to pattern 2. These findings suggest that the two appearances (thin and thick) of the cortex seen in PMG likely represent the same process, with the apparent difference being the result of myelination in subcortical and intracortical fibers that cause a change of the appearance and apparent thickness of PMG on T2-weighted images.